Neutrophil Extracellular Traps and NLRP3 Inflammasome: A Disturbing Duo in Atherosclerosis, Inflammation and Atherothrombosis - Puneetpal Singh; Nitin Kumar; Monica Singh; Manminder Kaur; Gurjinderpal Singh; Amit Narang; Abhinav Kanwal; Kirti Sharma; Baani Singh; Mario Di Napoli; Sarabjit Mastana (Vaccines, 2023)
Atherosclerosis is the formation of plaque within arteries due to overt assemblage of fats, cholesterol and fibrous material causing a blockage of the free flow of blood leading to ischemia. It is harshly impinging on health statistics worldwide because of being principal cause of high morbidity and mortality for several diseases including rheumatological, heart and brain disorders. Atherosclerosis is perpetuated by pro-inflammatory and exacerbated by pro-coagulatory mediators. Besides several other pathways, the formation of neutrophil extracellular traps (NETs) and the activation of the NOD-like receptor family pyrin domain containing 3 (NLRP3) inflammasome contribute significantly to the initiation and propagation of atherosclerotic plaque for its worst outcomes. The present review highlights the contribution of these two disturbing processes in atherosclerosis, inflammation and atherothrombosis in their individual as well as collaborative manner.